Video-Based Psychotherapy for Children and Adolescents: Patient Perspectives on Research Needs and Priorities - Elena von Wirth; Sarah Willems; Charlotte Hanisch; Tina In-Albon; Michael Kölch; Sarah K. Schäfer; Manfred Döpfner (Child Psychiatry & Human Development, 2026)
Abstract Telehealth plays an increasingly important role in mental healthcare, but empirical evidence regarding real-time, interactive psychotherapy for children and adolescents delivered via videoconferencing is limited. It has been suggested that research becomes more relevant, acceptable, and appropriate for service users when their research priorities are considered and that future studies should involve patients and their representatives in the planning and conduct of a trial. This study therefore aimed to identify patients’ research needs and priorities regarding video-based psychotherapy. Youths with experience in outpatient psychotherapy ( n = 33) and their parents ( n = 34) participated in the survey. Research questions relating to treatment effectiveness, the quality of the therapeutic relationship, side effects, and safety / privacy issues received high importance ratings, suggesting that these topics reflect patients’ and parents’ research needs. Parents prioritized research on the quality of the therapeutic relationship. Youths did not prioritize any of the proposed questions. However, patterns of research needs differed depending on youths’ personal experience with video-based psychotherapy. Several respondents used an open-ended comment box to indicate further research needs. This study adds valuable information on patient-reported research needs and priorities to the emerging field of digital technologies in mental healthcare. Future studies should not only investigate the course of patients’ symptoms and impairments during video-based psychotherapy, but also the therapeutic alliance, the frequency and impact of side effects, ways of delivering videoconference-delivered sessions in an engaging and effective way, safety/privacy issues, patient preferences, and whether video-based treatment improves youths’ access to healthcare.